Feedbacksløyfer og henvendthet: En revisjon av Fischer-Lichtes tese om gjensidig påvirkning av tilskuere og aktører i forestillinger - Böhnisch, Siemke (Peripeti, 2021)
This article reconsiders Fischer-Lichte’s concept of a so-called feedback loop in performances. In order to develop a systematical thesis that can be applied in performance analysis, Fischer-Lichte’s binary way of thinking is questioned. Actors’ and spectators’ mutual turning to the other is suggested to be decisive for the understanding of feedback loops. The differentiation of forms of turning to the other makes it possible to analyse differences between feedback loops, to connect these differences to genre conventions, and to acting and audience styles.